Nilai Adat Istiadat dalam Sunat Rasul di Gampong Gunung Pudung Kabupaten Aceh Selatan - Samwil Samwil; Fakhrul Rijal; Devi Martina (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study discusses the uniqueness and meaning contained in the traditions of the circumcision of the apostle. The researcher uses the symbolic interaction theory developed by Herbert Blummer to analyze the meaning of Symbolic Interaction in the Unique Portrait of the Implementation of the Circumcision of the Apostles in Gampong Gunung Pudung, Kluet Utara, Aceh Selatan. Theoretically, symbolic interaction is a social life which is basically human interaction using symbols. So a symbol is not formed through mental coercion, it arises because the meaning is given by humans themselves. The type of research used by the researcher is qualitative and the focus of this research is intended to limit studies that can facilitate researchers in managing data which then becomes a conclusion according to the formulated problem. The results of this study indicate that there are several unique customs of circumcision of the apostle in Gampong Gunung Pudung which are very different from other areas such as hitting canangs, asking for money from close relatives, washing rice into the river, carrying on shoulders or being lifted on a stretcher, bathing in the river and swing chickens and now they still maintain their ancestral culture.